Knowledge, Attitude and Practice Related to Chemotherapy Among Cancer Patients - Muzna Suhail MPhil; Fabeha Saulat PharmD; Hira Khurram PharmD; Farzeen Fatima PharmD; Atia Zenab PharmD; Mehak Wasim PharmD; Noor-; Fasiha Afzaal PharmD; Hamid Latif PharmD; Muhammad Nasrullah PharmD (SAGE Publishing, 2024)
Cancer is a leading cause of death, with a rapidly increasing global burden. Chemotherapy is the most effective cancer treatment, and with its benefits, there exist potential problems. The present study assesses cancer patients' knowledge, attitude, and practice toward chemotherapy use. A descriptive cross-sectional study was conducted in the oncology wards of various tertiary care hospitals and cancer care centers in Lahore, Pakistan. Patients were included in the study based on convenient sampling. A structured questionnaire with 25 (close-ended) questions and a demographic profile was used to collect data. Descriptive statistics was used to analyze frequencies and percentages. Independent sample t -test and ANOVA were used to calculate the mean and standard deviation. Most patients were females (54%) and married (52.6%), with an unemployment rate of 39%. Patients with higher education depicted significantly higher scores in knowledge (9.61 ± 2.65), attitude (19.37 ± 2.70), and practice (3.89 ± 1.03) domains. Surprisingly, throughout the whole KAP domain, the patient's attitude (18.42 ± 3.31) toward chemotherapy use, showed higher values, as compared to their knowledge (7.78 ± 3.26) and practice (3.66 ± 1.08) scores. The majority of the study participants had a positive attitude toward chemotherapy use, with limited knowledge, and practice.